Membangun kesadaran ramah lingkungan melalui program edukasi pengolahan sampah pada kelompok wanita tani Melati Berbah Yogyakarta - Khotim Hanifudin Najib; Afrizal Rafif Herdana; Amalia Harlin Hernanda Putri; Amalina Nur Hanifah; Arif Ardyatama; Noviana Dwi Rahmadani (Buletin Pengabdian Multidisiplin, 2024)
Purpose − The accumulation of improperly managed waste has become an urgent environmental issue in Indonesia. To address this, efforts to increase community awareness and knowledge regarding waste management are essential. This waste management education activity aims to enhance environmental awareness among members of the Melati Farmers' Group (KWT) in Berbah, Yogyakarta. Method − The activity was conducted on July 21, 2024, at the house of Mr. Suherman, RT 6 RW 2, Jragung Hamlet, Berbah, Sleman, DIY, involving 10 students as facilitators and 15 KWT Melati members as participants. The methods used in this activity included presenting waste management materials, interactive dialogues, Q&A sessions, and screening educational videos. At the end of the activity, an environmental awareness survey was conducted through a questionnaire consisting of 10 statements to measure changes in participants' knowledge and attitudes towards waste management. Findings − The results of the evaluation questionnaire processing showed that 40% of participants had high environmental awareness, while 60% had very high environmental awareness. Participants' enthusiasm for the materials presented was evident from their active participation in the discussion sessions and positive responses to the educational video screenings. These findings indicate that waste management education programs with interactive and visual approaches can effectively enhance environmental awareness in the community. It is hoped that through this activity, KWT Melati members can apply the waste management techniques they have learned, thereby contributing positively to their surrounding environment.